Geology of Canadian Wetlands - Warner, Barry (Geoscience Canada, 2004)
SUMMARY Wetlands have not gained as much attention as they ought to by geologists despite being so prevalent in the Canadian landscape. Some of this stems from a poor understanding of wetland geology and what wetland landforms are. Wetlands constitute unusual landforms in that they are formed of biological material predominantly shaped by biological processes rather than being formed of minerals and rock shaped more by physical processes. There are two main groups of wetlands: mineral wetlands, commonly situated in high-energy settings; and peatlands, situated in low-energy settings that undergo either terrestrialization or paludification during the course of their development. Wetlands, as both a landscape unit and economic resource, have historically been and will continue to be important in Canada. New and more specialized skills and engineering designs will be required to build infrastructure in wetland terrain. Wetlands should be regarded as an economic resource that requires wise use and management. Nature-sensitive technologies need to be invented for use with wetlands to conserve and enhance the resource to serve the needs and protect the health of human society.